2016
DOI: 10.1177/0019793916657538
|View full text |Cite
|
Sign up to set email alerts
|

Complementarities between Employee Involvement and Financial Participation

Abstract: The authors investigate whether productivity is greater if firms use employee involvement (EI) in decision making and financial participation (FP) as complementary practices. Based on representative panel data from Finnish manufacturing firms, the study uses diverse specifications to examine different theoretical explanations of the productivity effects of complementarities. The authors find virtually no evidence to support the theory of complementarities when EI and FP are simply measured by their incidence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 46 publications
0
3
0
1
Order By: Relevance
“…To avoid this, companies should consider involving trade unions in the adoption of incentive schemes to ensure transparency and sufficient employee onboarding. Jones et al (2012bJones et al ( , 2017 found that employee involvement or direct participation through trade unions fostered financial participation and provided meaningful incentives to motivate employees in achieving performance targets. In another study, Antonietti et al (2017) confirmed that trade unions' presence in the workplace influences shared decision-making in the adoption of flexiblepay systems or incentive schemes aimed at improving employee productivity.…”
Section: Incentive-induced Employee Productivitymentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid this, companies should consider involving trade unions in the adoption of incentive schemes to ensure transparency and sufficient employee onboarding. Jones et al (2012bJones et al ( , 2017 found that employee involvement or direct participation through trade unions fostered financial participation and provided meaningful incentives to motivate employees in achieving performance targets. In another study, Antonietti et al (2017) confirmed that trade unions' presence in the workplace influences shared decision-making in the adoption of flexiblepay systems or incentive schemes aimed at improving employee productivity.…”
Section: Incentive-induced Employee Productivitymentioning
confidence: 99%
“…Determining employee participation in the financial wellbeing of organisations through monetary or non-monetary incentives is important for examining how extrinsic and intrinsic motivation lead to productivity. Studies investigating monetary or non-monetary incentive schemes have been instrumental in our understanding of employee productivity and organisational performance (Adewuyi & Effiong, 2017;Adom et al, 2020;Aguinis et al, 2013;Antonietti et al, 2017;Damiani et al, , 2016Daniel, 2019;Gielen et al, 2010;Jones & Kato, 2012;Jones et al, 2008Jones et al, , 2010Jones et al, , 2012Jones et al, , 2017Kalmi & Sweins, 2010;Kato & Kauhanen, 2018;Kato et al, 2010;Lucifora & Origo, 2015;Mullins, 2022;Ortlieb et al, 2016;Park et al, 2022;Sesil & Lin, 2011;Sgarbossa et al, 2022;Singh & Chaudhary, 2022;Ude & Coker, 2012;Yang & Chen, 2019;Yoon & Sengupta, 2021). However, there is a lack of empirical knowledge in South Africa with findings on incentiveinduced employee productivity focusing on the monetary and non-monetary components using panel data analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Por su parte, Chun & Lee (2015), al igual que en Konings y Vanormeligen (2015) y Jones et al (2017), relacionaron esta productividad con las prácticas de compensación, encontrando una alta y significativa relación, apoyando con ello la hipótesis de que la ausencia de buenas prácticas e incentivos, puede ser uno de los factores que han limitado incrementos en la productividad del sector manufacturero.…”
Section: Productividad Industrial Y Maderera Evidencia Empíricaunclassified
“…In addition, corporate financial performance can be measured by corporate profitability, corporate operating capacity, corporate labor productivity, etc. (Ayuningtyas and Misnaniarti, 2016;Jones et al, 2016). Based on both resource-based theory and empirical results, it is possible that employee direct involvement is positively associated with corporate financial performance.…”
Section: Employee Direct Involvement and Corporate Performancementioning
confidence: 99%